Controls over the strength and timing of fire–grazer interactions in a semi‐arid rangeland. Issue 1 (20th December 2013) - Augustine, David J.; Derner, Justin D.; Morgan, Eric
Summary The degree to which large herbivores select and forage within recently burned areas is a key driver of vegetation heterogeneity in rangeland ecosystems. However, few studies have quantified the strength and timing of herbivore selection for burned areas or examined how selection strength varies among ecosystems differing in precipitation and primary productivity. We conducted a 4‐year patch‐burning experiment in semi‐arid rangeland of Colorado, USA, where 25% of the area available to cattle was burned each year and burned patches were shifted annually. We used GPS collars with activity sensors to quantify the distribution of free‐ranging cattle at a high temporal resolution (5‐min intervals) during the growing season each year. We used a classification tree model to discriminate between cattle grazing vs. non‐grazing locations, which significantly increased precision in quantifying burn selection strength. We fit generalized linear models predicting the frequency of cattle use of a given location within each study area and month, enabling comparisons between the relative influence of burns and topography on grazing distribution. Across multiple growing seasons, cattle selectively spent 31% of grazing time on recently burnt areas, which comprised 25% of the landscape; this selection strength was half as strong as that documented in mesic rangeland. At a monthly temporal scale, strong cattle selection for burned areas occurred during periods of rapid vegetation growth regardless of when during the growing season this greening occurred. Outside these intervals, burn selection strength was inconsistent and cattle grazing distribution was primarily influenced by topography. Thus, the relative importance of fire and topography in controlling grazer distribution was temporally contingent upon the timing and size of precipitation pulses. Synthesis and applications. Spatiotemporal interactions between fire and herbivores are a consistent feature of both semi‐arid and mesic rangelands, with interaction strength varying across gradients of precipitation and primary productivity. Management of semi‐arid ecosystems to sustain ecological processes should include strategies that allow ungulate herbivores to shift their grazing distribution seasonally in response to fire, topoedaphic variation and precipitation patterns. Combined management of fire and grazing for conservation objectives can be consistent with, and even complementary to, livestock production goals.